Pulmonary Pathologies Following Inhalation of Multi-Walled Carbon Nanotubes at Occupational Levels - Phipps, Marshal Anthony, Jr. (East Carolina University)
Multi-walled carbon nanotubes (MWCNT) are a nanomaterial that is growing in use and popularity. The health effects of occupational pulmonary exposure to MWCNT are currently unknown. The goals of this study were to build a dust generator capable of producing occupational levels of MWNCT and to examine pulmonary effects of occupational levels of inhaled dry MWCNT. We designed, built, and tested a dust generator capable of producing MWCNT concentrations in the occupational exposure range (25,000 to 50,000 particles/cm3). In a time course study, C57BL/6J male mice were exposed to either a dust of MWCNT at a daily average of approximately 37,000 particles/cm3 and a daily peak of about 50,000 particles/cm3 or to air alone. Six mice per group were exposed for 4 hours per day for 5 days a week for 2 weeks and sacrificed 1, 3, 7, 10, 14, 28, and 84 days post-exposure. In a strain comparison study DBA/2J and A/J mice underwent the same exposure and were sacrificed at 14 days post-exposure. For both studies bronchoalverlavage (BAL) fluid was collected to assess cellular profile and protein content. The right lung was used for collagen measurement. The left lung was used for histological evaluation. Total protein, a measure of lung permeability, did not change significantly after MWCNT exposure compared to air controls at any time point. Likewise, eosinophil and neutrophil cell counts were not significantly different between air and MWCNT-exposed mice. However, compared to air controls, MWCNT-exposed mice had increased numbers of total cells and macrophages at 28 days post exposure and increased monocytes from 10 to 14 days exposure. The presence of MWCNT was visually noted in BAL cell pellets, histology slides, and lung homogenate membrane pellets at all of the time points. Dark field microscopy showed MWCNT in BAL cells at all of the time points in MWCNT exposed mice. Collagen levels were not different between exposure groups at any time point. The strain comparison found that C57BL/6J mice had increases in monocytes an lymphocytes at 14 days post exposure and A/J mice showed a trend towards an increase in lung protein levels in MWCNT exposed mice at 14 days post exposure. MWCNT were visually detected in lung homogenate membrane pellets and in the histology slides from all strains. Although short-term inhalational exposure to occupationally relevant levels of dry dusts of MWCNTs did not elicit significant increases in measures of lung injury or fibrogenesis, increases in mononuclear cells and lack of particle clearance may indicate an altered host-defense capacity which could lead to disease with further particle accumulation or subsequent pathogen exposure.
Keywords: Toxicology; Occupational safety; Physiology; MWCNT; Administration, Inhalation; Lung; Nanotubes, Carbon